Corruption and Cryptocurrency: Blockchains as corruption tools. - Ibrahimi, Adrianit; Arifi, Besa (Academicus, 2022)
Cryptocurrency has become ubiquitous and is evolving constantly. The question is if our legal framework is catching up with it. Therefore, this article analyzes the arguments on the legitimacy and legality of cryptocurrency in order to emphasize the relation between corruption and cryptocurrency. The research has enlightened some cogent arguments on the possibility of perpetrators committing corruption acts through cryptocurrency. These arguments basically refer to some of the unique characteristics of cryptocurrency such as the quick value fluctuation, the difficulties in tractability and the lacking current legislation. The unique features of it may headline cryptocurrency as an immensely attractive environment for corruption activities. Hence the world has already faced some tangled scamming scandals with cryptocurrency specified herein. Therefore, the aim of this article is to highlight the possibility for corruption acts to be committed through cryptocurrency as a form of corruption unknown before.